1985
DOI: 10.1001/jama.1985.03350280091026
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Pontiac Fever Related to Whirlpool Use, Michigan 1982

Abstract: Fourteen of 23 female members of a church group experienced an acute self-limited illness characterized by chills, fever, chest pain, cough, and nausea, consistent with the diagnosis of Pontiac fever. All 14 affected women had used a whirlpool located in the women's locker room during a racquetball party. Legionella pneumophila serogroup 6 was isolated from the women's whirlpool. Nine of 14 cases showed a seroconversion to heat-fixed antigen prepared from the L pneumophila serogroup 6 isolate. Aerosol size stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

1985
1985
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…These findings indicated that both were sporadic community-acquiredcases but not epidemics. Here, wereported the first sporadic cases of Pontiac fever in Japan, although Pontiac fever has been found in many epidemics (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). It is important to recognize such cases associated with acute onset of high fever, and the late development of bilateral pleural effusion, which in the present cases, was not responsive to the typical antibiotic therapy.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…These findings indicated that both were sporadic community-acquiredcases but not epidemics. Here, wereported the first sporadic cases of Pontiac fever in Japan, although Pontiac fever has been found in many epidemics (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). It is important to recognize such cases associated with acute onset of high fever, and the late development of bilateral pleural effusion, which in the present cases, was not responsive to the typical antibiotic therapy.…”
Section: Discussionmentioning
confidence: 63%
“…Pontiac fever, non-pneumonic legionellosis has been found in many recent epidemics (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Girod et al discussed that not only epidemics but also sporadic cases of nonpneumonicillness mayrepresent a bridge between subclinical illness and pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Legionella pneumophila serogroup 6 was found to be the cause of t wo Pontiac lever outbreaks associated with whirlpools. 1 In one investigation, the duration of fever was directly related to length of exposure to the aerosols created bythe induced water turbulence of the whirlpool bath. Limited studies on aerosol particles generated in aerated water suggest the droplets in the air over a whirlpool are small enough (0.5 to 8.0 u.m) to be inhaled and reach the lungs; droplets of 2 u,m or larger could cany Legionella, if present.…”
Section: Epidemiologic Recordmentioning
confidence: 99%